AB0274 Correlation of CDAI and SDAI with das in a large real-life cohort of RA patients treated with infliximab. (23rd January 2014) - Choquette, D.; Bensen, W.; Baker, M.; Sampalis, J.; Otawa, S.; Khalil, S.
Abstract : Objectives: In recent years, the efficacy of anti-TNF-alpha in the management of RA has been demonstrated in numerous controlled clinical trials. The Clinical Disease Activity Index (CDAI) and Simplified Disease Activity Index (SDAI) have been recently designed as simplified disease activity scores. The purpose of this analysis is to evaluate the correlation between these simplified disease activity scores and routine clinical practice scores. Methods: The data for this analysis were obtained from an observational study of adult RA patients initiated on treatment with infliximab and followed prospectively as per routine care since 2002. The majority of patients enrolled were biologic naïve. Results: A total of 440 patients were included in this analysis. Mean (SD) age was 56.4 (13.6) years and mean (SD) disease duration at baseline was 11.0 (10.2) years. Mean SDAI, CDAI, DAS28-CRP and HAQ scores decreased significantly over 48 months (p<0.001, for all parameters). A statistically significant strong positive correlation was observed between the DAS28-CRP and the SDAI (r=0.82; p<0.001) or CDAI (r=0.94; p<0.001). Differences in the proportion of patients achieving low disease activity (LDA) and remission were observed between DAS28-CRP, SDAI and CDAI. Conclusions: The results of this real-life observational study demonstrate that over four years of treatment infliximab is effective in reducing symptom severity and improving outcomes in patients with Rheumatoid Arthritis using different scores. DAS28 classified more patients in remission compared to the more strict SDAI and CDAI definitions, in agreement with previous studies. Also, the data from this registry confirmed the validity of the SDAI and CDAI as disease activity measures in a real-life RA cohort. Disclosure of Interest: None Declared